Adsorption of antibiotics on microplastics. (June 2018) - Li, Jia; Zhang, Kaina; Zhang, Hua
Abstract: Microplastics and antibiotics are two classes of emerging contaminants with proposed negative impacts to aqueous ecosystems. Adsorption of antibiotics on microplastics may result in their long-range transport and may cause compound combination effects. In this study, we investigated the adsorption of 5 antibiotics [sulfadiazine (SDZ), amoxicillin (AMX), tetracycline (TC), ciprofloxacin (CIP), and trimethoprim (TMP)] on 5 types of microplastics [polyethylene (PE), polystyrene (PS), polypropylene (PP), polyamide (PA), and polyvinyl chloride (PVC)] in the freshwater and seawater systems. Scanning Electron Microscope (SEM) and X-ray diffractometer (XRD) analysis revealed that microplastics have different surface characterizes and various degrees of crystalline. Adsorption isotherms demonstrated that PA had the strongest adsorption capacity for antibiotics with distribution coefficient ( K d ) values ranged from 7.36 ± 0.257 to 756 ± 48.0 L kg −1 in the freshwater system, which can be attributed to its porous structure and hydrogen bonding. Relatively low adsorption capacity was observed on other four microplastics. The adsorption amounts of 5 antibiotics on PS, PE, PP, and PVC decreased in the order of CIP > AMX > TMP > SDZ > TC with K f correlated positively with octanol-water partition coefficients (Log Kow ). Comparing to freshwater system, adsorption capacity in seawater decreased significantly and no adsorption was observed for CIP and AMX. Our results indicated that commonly observed polyamide particles can serve as a carrier of antibiotics in the aquatic environment. Graphical abstract: Image 1 Highlights: Adsorption behaviors of 5 antibiotics on 5 MPs in freshwater and seawater are studied. Polyamide (PA) has high adsorption for antibiotics and may serve as pollutant carrier. Adsorption on PE, PS, PP, and PVC decreased in the order of CIP > AMX > TMP > SDZ > TC. Higher adsorption of antibiotics on MPs in the freshwater than in seawater.